PENGARUH TAYANGAN VIDEO TIK TOK PRODUK PERAWATAN KULIT TERHADAP PERILAKU KONSUMTIF GENERASI MILENIAL - Indah Handaruwati; Lyna (JURNAL MARITIM, 2024)
ABSTRACT This study aims to analyze the effect of Skin Care Product Reviews on the Tik Tok application on consumer behavior in the millennial generation. The population in this study were all active female students of both state and private universities, the sample was taken using purposive sampling and convenience sampling techniques. The sample used in this study was 100 respondents. Data collection using a questionnaire. Data analysis was performed by testing multiple linear regression analysis. The results of the study show that broadcast content has a significant effect on consumptive behavior. Watching intensity has no significant effect on consumptive behavior. Product attractiveness has a significant effect on consumptive behavior, source credibility has a significant effect on consumptive behavior. Viewing Content, Viewing Intensity, Product Attractiveness, and Source Credibility simultaneously influence consumptive behavior. The hypothesis which states that product attractiveness is the dominant variable is not proven because the highest coefficient results are in the source credibility variable.